Inhibition of corrosion of mild steel by an alcoholic extract of a seaweed Sargassum muticum - Suyambulingam Jone Kirubavathy; Hashem Abdulhameed Al; Rajendran Susai Santhammal; R.M. Joany; Časlav Lačnjevac (Zaštita Materijala)
An alcoholic extract of a sea weed Sargassum muticum has been used to control corrosion of mild steel in 0.5 N HCl. Weight loss method and Electrochemical studies have been used in this study. Weight loss study reveals that 500 ppm of the inhibitor offers 99.25 % inhibition efficiency. Polarization study reveals that the inhibitor functions as an anodic inhibitor at higher concentration. The AC impedance spectra confirm the formation of a protective film on the metal surface. Adsorption of inhibitor molecules on the metal surface follows Langmuir adsorption isotherm.